Recent Developments of Mn(II)-Doped 2D-Layered and 2D Platelet Perovskite Nanostructures - Das Adhikari, Samrat; Pradhan, Narayan (Frontiers in Materials, 2020)
2D layered perovskites are recently emerged as one of the most promising materials for optoelectronics. These not only behave like a quantum well structures but also on doping Mn(II) ions at the Pb-site results highly emissive doped material. These structures can also be used as a starting material for obtaining 3D perovskites. Thermal treatment of Mn(II) incorporated layered perovskites in presence of Cs(I) ions led to Mn(II)-doped 2D platelets shaped perovskites, which also tune their dimensions with varying the dopant ion concentration. Keeping the importance of the 2D layered perovskites, this review focused on the basic structures to the recently developed synthetic strategies and their optical properties of layered structured perovskites, Mn(II)-doped layered perovskites and Mn(II)-doped 2D platelet shaped perovskites.